(untitled) (Revista científica Olimpia, 2019)
The present project emphasizes the technical elements that need to be taught in a quick time in events similar to the real ones. That based on a good perception that the individual has of the ball, the most essential tactical technical skills should be elaborated, in all details be great or minimum. The tactic composes situations that integrate the opposing team, which involves the fact that the game requires tactical principles that are defined as a set of rules that imply that the game provides players the ability to achieve quickly. tactical solutions to the different problems developed by the situation they face.